Ordinance No. 12: An Ordinance to Suppress Criminal and Improper Practices in the City of Beloit, in BELOIT WEEKLY DEMOCRAT, May 16, 1879, at 4, § 31 - (:unkn) unknown (My University, 1879)
§ 31: That any person who shall within said city, carry concealed on or about his or her person, a revolver, pistol, bowie-knife, dirk, slung-shot, brass, lead or iron knuckles, or any other dangerous weapon, shall be deemed guilty of a misdemeanor.
Keywords: CARRY - CONCEALED